2007
DOI: 10.1007/s00419-007-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear analysis and solitary waves for two superposed streaming electrified fluids of uniform depths with rigid boundaries

Abstract: The nonlinear modulation of the interfacial waves of two superposed dielectric fluids with uniform depths and rigid horizontal boundaries, under the influence of constant normal electric fields and uniform horizontal velocities, is investigated using the multiple-time scales method. It is found that the behavior of small perturbations superimposed on traveling wave trains can be described by a nonlinear Schrödinger equation in a frame of reference moving with the group velocity. Wave-like solutions to this equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…IV, this means that the influence of nonlinearity shifts the time of singularity formation by ∼ |S| 1/2 . Note that in the case of such dependence of on the parameter S, even the rough estimate for the surface-slope angles (22) predicts the formation of strong singularities violating the small-angle approximation. In accordance with (29), the boundary shape becomes singular at the moment t = t c : η(x,t c ) = πSδ(x), where δ(x) is the Dirac δ function.…”
Section: Dynamics Of the Interface For A E = −Amentioning
confidence: 98%
See 1 more Smart Citation
“…IV, this means that the influence of nonlinearity shifts the time of singularity formation by ∼ |S| 1/2 . Note that in the case of such dependence of on the parameter S, even the rough estimate for the surface-slope angles (22) predicts the formation of strong singularities violating the small-angle approximation. In accordance with (29), the boundary shape becomes singular at the moment t = t c : η(x,t c ) = πSδ(x), where δ(x) is the Dirac δ function.…”
Section: Dynamics Of the Interface For A E = −Amentioning
confidence: 98%
“…As a rule, the resulting equations are nonlocal (i.e., they contain integrodifferential operators), which seriously hampers their analysis. In most publications, nonlinear waves on the surface of dielectric or conducting fluids are considered under the assumption that the characteristic wavelength is much larger than the depth of the fluid layer [7][8][9][10][11][12][13][14][15] or that the excited wave packet is spectrally narrow [6,[16][17][18][19][20][21][22][23]. Both approaches make it possible to reduce the original problem to the consideration of relatively simple local partial differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that A depends on x 2 , y 2 , and t 2 through the transformation ␥ 2 ϭ k Ϫ1 ͓͑k x x 2 ϩ k y y 2 ͒ Ϫ ͑k x k x ϩ k y k y ͒t 2 ͔ and = t 2 [7], we obtain finally from (34) the following nonlinear Ginzburg-Landau equation with complex coefficients:…”
Section: The Nonlinear Ginzburg-landau Equationmentioning
confidence: 99%
“…They found that the electric field plays a dual role in the stability criterion in the sense that it stabilized perturbations having relatively small wavenumbers if the dielectric constant of the upper fluid is smaller than that of the lower fluid and vice versa. For recent developments of this topic, see the investigations of El-Sayed and co-workers [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…It was shown that the complex amplitude of a quasi-monochromatic traveling wave can be described by a nonlinear Schrö dinger equation in a frame of reference moving with the group velocity. For a recent developments of this topic, see the investigations of Papageorgiou and Petropoulos (2004), Shankar and Sharma (2004), Tomar et al (2007), Ugug and Aubry (2008), El-Sayed (2008), and Yecko (2009. It should be noted that in all the above-mentioned studies, the medium has been considered to be nonporous.…”
Section: Introductionmentioning
confidence: 98%